2020
DOI: 10.2147/ott.s235944
|View full text |Cite
|
Sign up to set email alerts
|

<p>Bioactive Compounds from <em>Abelmoschus manihot L</em>. Alleviate the Progression of Multiple Myeloma in Mouse Model and Improve Bone Marrow Microenvironment</p>

Abstract: Abelmoschus manihot (L.) Medik. (Malvaceae) derived Huangkui capsules (HKC) represent a traditional Chinese medicine that has been widely applied to the clinical therapy of kidney and inflammatory diseases. The present study aimed to determine the potential therapeutic effects and underlying mechanisms of the ingredients on Multiple Myeloma (MM), an incurable disease that exhibits malignant plasma cell clonal expansion in the bone marrow. Methods: A 5TMM3VT syngeneic MM-prone model was established and treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
(59 reference statements)
0
13
0
Order By: Relevance
“…However, more evidence is needed to obtain detailed structural information as well as the mechanism of action of AMPS-a and explore it as a potential antitumor agent. In a recent study, Hou et al. (2020) found that HKC, at 3.75 g/kg/day, prominently prolonged the survival rate of a multiple myeloma-prone mouse model.…”
Section: Pharmacological Activitiesmentioning
confidence: 97%
See 2 more Smart Citations
“…However, more evidence is needed to obtain detailed structural information as well as the mechanism of action of AMPS-a and explore it as a potential antitumor agent. In a recent study, Hou et al. (2020) found that HKC, at 3.75 g/kg/day, prominently prolonged the survival rate of a multiple myeloma-prone mouse model.…”
Section: Pharmacological Activitiesmentioning
confidence: 97%
“…Further phytochemical investigations proved that four bioactive ingredients from HKC, namely hyperoside (28), cannabiscitrin (29), 8-(2′′-pyrrolidione-5-yl)-quercetin (48), and 3- O -kaempferol-3- O -acetyl-6- O -(p-coumaroyl)-β-D-glucopyranoside (49), at concentrations of 0.05 and 5 μM, notably promoted the differentiation of murine pre-osteoblast MC3T3-E1 cells ( Hou et al., 2020 ). Furthermore, compound (49) suppressed the proliferation of multiple myeloma ARP1 and H929 cells and induced cell cycle arrest at G 0 /G 1 phase, which may be related to inhibition of the β-catenin protein, upregulation of the expressions of IL-6 and TNF-α, as well as activation of mature TGF-β1 ( Hou et al., 2020 ). The results from this study indicated that HKC exerts protective effects and may serve as a promising anti-multiple myeloma drug.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 10 ] Huangkui capsule has applied to treat DN for about 10 years in clinical practice with no reported adverse reactions. [ 11 , 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…The latest clinical MM therapy is a new immunomodulatory therapy using chimeric antigen receptor T cells, bispecific T cell conjugates, and immune checkpoint inhibitors (6). Although the therapeutic armamentarium for MM has continued to evolve (7)(8)(9)(10)(11)(12)(13)(14), MM still possesses the characteristics of high relapse and incurability. It is necessary to explore more effective therapies to improve MM prognosis significantly.…”
Section: Introductionmentioning
confidence: 99%